HOW ASSET GROWTH, EARNINGS VOLATILITY, FIRM SIZE, AND LEVERAGE AFFECT STOCK PRICE VOLATILITY - Rangga, Adrianus; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to examine how asset growth, leverage, firm size, and earnings volatility affect stock price volatility. 30 LQ-45 enterprises that had been registered for three consecutive years, from 2018 to 2020, made up the study's sample. In this work, multiple regression analysis is used for hypothesis testing. E-views version 12 is the program used for data processing in this study. According to the study's findings, factors affecting firm size can affect stock price volatility, while factors affecting leverage, earnings volatility, and asset growth cannot.